2010
DOI: 10.1029/2009ja014907
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous FAST and Double Star TC1 observations of broadband electrons during a storm time substorm

Abstract: [1] Broadband electrons (BBEs) exhibit remarkable electron flux enhancements over a broad energy range (0.03-30 keV) near the equatorward edge of the auroral oval during geomagnetic storms. Here, we report a BBE event observed by the Fast Auroral Snapshot (FAST) satellite at 1355-1359 UT, ∼61°-66°invariant latitudes, ∼0600 magnetic local time (MLT), and ∼3800 km altitude during a storm on 25 July 2004. The Double Star (DS) TC1 satellite was located near the magnetic equator at L = 5.7, close to the same local … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Broadband electron precipitation has a complicated relationship with ambient plasma density [see Alm et al , , and references therein]. Broadband electron precipitation may carry a significant amount of FAC [e.g., Nakajima et al , ], sometimes comparable to that carried by monoenergetic electron precipitation [ Semeter et al , ]. However, the integrated effect on large‐scale FAC system is small [ Andersson et al , ].…”
Section: Introductionmentioning
confidence: 99%
“…Broadband electron precipitation has a complicated relationship with ambient plasma density [see Alm et al , , and references therein]. Broadband electron precipitation may carry a significant amount of FAC [e.g., Nakajima et al , ], sometimes comparable to that carried by monoenergetic electron precipitation [ Semeter et al , ]. However, the integrated effect on large‐scale FAC system is small [ Andersson et al , ].…”
Section: Introductionmentioning
confidence: 99%
“…Shiokawa et al ., indicated that broadband electrons can cause low‐latitude red auroras during storm‐time substorms. The broadband electrons are the electron precipitation observed by Defense Meteorological Satellite Program and Fast AuroralSnapshoT satellites over a broad energy range of ∼ 30 eV to 30 keV at subauroral latitudes [ Shiokawa et al ., ; Nakajima et al ., , , ]. However, simultaneous measurements of low‐latitude red auroras on the ground and plasma characteristics by magnetospheric and low‐earth orbit satellites are still very rare.…”
Section: Introductionmentioning
confidence: 99%